Effects of lifestyle modification on liver enzyme and Fibroscan in Indian patients with non-alcoholic fatty liver disease - Paul, Jayanta (Gastroenterol Rep (Oxf), 2018)
BACKGROUND AND AIMS: Non-alcoholic fatty liver disease (NAFLD) is remarkably increasing in developing countries like India, in parallel with the increasing incidence of obesity. Lifestyle modification is a recommended treatment for NAFLD. In most of the previous studies, improvement after lifestyle modification was assessed by liver fibrosis through liver biopsy, but we cannot do a serial liver biopsy in every NAFLD patient. Liver fibrosis can also be assessed by fibroscan non-invasively in NAFLD. This study was designed to evaluate the effect of lifestyle modification on liver enzymes and Fibroscan values in a population with NAFLD. METHODS: Initially, 50 NAFLD patients were included in this prospective follow-up study; however, after 6 months of lifestyle modification, only 39 participants were studied. During both the first and second consultations, Fibroscan was carried out. All participants underwent a careful interview, anthropometry measurements and radiological and biochemical tests during every consultation. RESULTS: After 6 months of lifestyle modification, Fibroscan values improved significantly (8.31 ± 0.11kPa vs 7.87 ± 0.12kPa, p=0.009). Alanine aminotransferase (ALT) values also showed improvement during the second consultation (97.25 ± 2.62 U/L vs 66.69 ± 3.95 U/L, p <0.001). CONCLUSION: Measured by Fibroscan and liver enzymes, it has been found that lifestyle modification is an effective therapy to downgrade hepatic injury in NAFLD patients. Serial Fibroscan can be used to assess the treatment response in NAFLD patients due to its non-invasive nature.